Wounded Thinking of the Wounded World. Nihilism and Global Warming - Susanna Lindberg (Phainomena)
The article claims that one of the most important tasks of thinking today is global warming. Can it be analyzed as another form of nihilism: not as nihilism of the meaning of life, but as a new kind of nihilism of human and nonhuman life itself? Could global warming be analyzed as a kind of “objective nihilism” tied to the active nihilism of humankind that causes it and to the passive nihilism of humankind that endures it, rather than acting against it? This article attempts to explain “the objective nihilism” of global warming with the help of Maurice Blanchot’s term “disaster,” by showing how it leads to the nihilistic attitudes of despair and indifference. It also asks how the lucidity of nihilism can be turned into a force.